PERANAN METABAHASA SEMANTIK ALAMI DALAM PENCARIAN MAKNA VERBA BAHASA BALI “RASA PADA ANGGOTA TUBUH” - Ni Nyoman Tri Sukarsih; Ni Made Diana Erfiani (SPHOTA: Jurnal Linguistik dan Sastra, 2014)
ABSTRACT The Balinese verb 'to feel' can be expressed through various lexicons, which have the same field of meaning, namely physical pain in the limbs. Using the MSA (Natural Semantics Metalanguage) approach it can be revealed that each lexicon has a different meaning, even though they are on the same meaning field. This happens because the semantic features of every lexicon can be described through an in-depth study of metalanguage, namely by revealing the characteristics of its semantic primes so that even subtle differences in meaning can be mapped. The NSM theory is able to discern subtle differences between meanings,and so support the postulate, which is one form for one meaning and one meaning expressed by a single lexicon. Keywords: Verb to Feel, Natural Sematics Metalanguage